Case Report: Wide Spectrum of Manifestations of Ligase IV Deficiency: Report of 3 Cases - Castro, Ana Costa e; Maia, Raquel; Batalha, Sara; Freixo, João Parente; Martins, Catarina; Neves, Conceição; Cordeiro, Ana Isabel; Neves, João Farela (Frontiers in Immunology, 2022)
DNA ligase IV deficiency is a rare autosomal recessive disorder associated with impaired DNA repair mechanisms. Most patients with DNA repair defects present with neurologic deficits, combined immunodeficiency, bone marrow failure and/or hematologic neoplasia. We present 3 unrelated cases of ligase IV deficiency with different clinical presentations. Patient 1 presented at the age of 5 years-old with bone marrow failure, dysmorphic features and T and B.lymphopenia. A compound heterozygous variant L19W/K635fs in LIG4 gene was identified. Patient 2 presented at the age of 16-years with recurrent infections. He had agammaglobulinemia and absent B-cells. A homozygous R278H in LIG4 gene was identified. Patient 3 was referred for vitiligo and B-cell lymphopenia (low class-switched B-cells) and hypogammaglobulinemia. Homozygous R278H in LIG4 was also identified. In the last few years, the spectrum of clinical manifestations caused by ligase IV deficiency has widened, making it very difficult to establish accurate clinical diagnosis. The use of NGS has allowed proper diagnosis that provided better prognosis and adequate family counselling.